CHARACTERISTICS OF THE ARABIAN GULF ENVIRONMENT AND ITS IMPACT ON CONCRETE DURABILITY – AN OVERVIEW - Al-Gahtani, A.S. (2020)
The environmental conditions of the Arabian Gulf that are characterized by high temperature and humidity significantly affect the performance of concrete structures in this region. The daily and seasonal variations in the temperature and humidity further accelerate the rate of concrete deterioration which is predominantly exhibited in the form of reinforcement corrosion, sulfate attack, salt scaling and cracking due to plastic and drying shrinkage. The high humidity provides moisture to concrete that is essential for reinforcement corrosion. Further, the temperature and humidity regimes that are commonly noted in this region are conducive for accelerated carbonation of concrete. The geomorphic conditions in the coastal areas of the Arabian Gulf that are characterized by shallow groundwater table, groundwater and soil contaminated with high concentrations of both chloride and sulfate salts also accelerate the deterioration of concrete mainly due to reinforcement corrosion, sulfate attack and salt weathering. This paper discusses the effect of environmental conditions, namely temperature, humidity, blowing wind, shallow groundwater and high salinity of the groundwater and soil, of the Arabian Gulf, on concrete durability.